Solve equation y^((iv))+y=1 with Laplace

Oscar Burton 2022-10-14 Answered
Solve equation y ( i v ) + y = 1 with Laplace
with           y ( 0 ) = y ( 0 ) = y ( 0 ) = y ( 0 ) = 0
I got
Y ( s ) = 1 s ( s 4 + 1 )
But, I don't know how to continue:
s 4 + 1 = ( s 2 + 2 s + 1 ) ( s 2 2 s + 1 )
You can still ask an expert for help

Want to know more about Laplace transform?

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Kenley Rasmussen
Answered 2022-10-15 Author has 13 answers
Hint: As you wrote, by taking Laplace from your equation, we obtained
Y ( s ) = 1 s ( s 4 + 1 )
Then, using partial fractions, we have
Y ( s ) = 1 s s 3 s 4 + 1
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2021-12-26
Eliminate the arbitrary constants:
y=c1ex+c2xex
asked 2021-10-15
A boat is pulled into a dock by a rope attached to the bow of the boat and passing through a pulley on the dock that is 1 m higher than the bow of the boat. If the rope is pulled in at a rate of 1 m/s, how fast is the boat approaching the dock when it is 8 m from the dock?
asked 2021-02-01
Find Laplace transform for
x"3x+2x=1e2t
asked 2022-11-11
Find the inverse Laplace transform of the following:
F ( s ) = 2 s + 1 s 2 2 s + 2 .
The answer is f ( t ) = 2 e t cos t + 3 e t sin t
Obviously once you have the decomposed fraction the remainder of the problem is simple but I can't seem to get to that point. Could someone please lay out the steps to decompose F(s)?
asked 2022-09-14
L ( ( t + 5 ) U ( t 1 ) ) = U ( t a ) f ( t a ) = e a s F ( s )
a= 1
I am having trouble dealing with f ( t a ) and finding F ( s )
f ( t 1 ) = e t 3 = e ( t 1 ) 3 + 1 = e ( t 1 ) 2
f ( t ) = e t 2
How do I Laplace transform this ?
asked 2022-11-19
The Laplace transform of L ( t e t cos t )
How do I find it?
asked 2022-11-02
Find:
L ( t 2 e t u ( t 6 ) )
My trying
L ( F ( t a ) u ( t a ) ) = e a s F ( s ) L ( t f ( t ) ) = d d s f ( s ) L ( t 2 f ( t ) ) = d 2 d s 2 f ( s )
Then:
L ( t 2 e t u ( t 6 ) ) d 2 d s 2 ( e t u ( t 6 ) ) e t u ( t 6 )
L ( e t u ( t 6 ) ) = e 6 s 1 s 1
is my attempt correct ??